2015
DOI: 10.1089/neu.2014.3743
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotection, Plasticity Manipulation, and Regenerative Strategies to Improve Cardiovascular Function following Spinal Cord Injury

Abstract: Damage to the central nervous system, as in the case of spinal cord injury (SCI), results in disrupted supraspinal sympathetic influence and subsequent cardiovascular control impairments. Consequently, people with SCI suffer from disordered basal hemodynamics and devastating fluctuations in blood pressure, as in the case of autonomic dysreflexia (AD), which likely contribute to this population's leading cause of mortality: cardiovascular disease. The development of AD is related, at least in part, to neuroanat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 75 publications
(190 reference statements)
1
6
0
Order By: Relevance
“…In vivo and in vitro studies have shown that, following spinal cord injury (SCI), a substantial number of spinal neurons survive despite severe symptoms of motor and sensory deficit arising from the secondary lesion process that extends, within the first 24 hr, the pathological degeneration to initially spared spinal areas (Ahuja et al., ; Dell'Anno & Strittmatter, ; Filous & Schwab, ; Kuzhandaivel, Nistri, Mazzone, & Mladinic, ; Quraishe, Forbes, & Andrews, ). This observation is corroborated by clinical studies (Hoh, Mercier, Hussey, & Lane, ; Kaelan, Jacobsen, & Kakulas, ; Squair, West, & Krassioukov, ). The question then arises about the nature of the intrinsic protective mechanisms that can avoid a more extensive neuronal damage.…”
Section: Introductionsupporting
confidence: 66%
“…In vivo and in vitro studies have shown that, following spinal cord injury (SCI), a substantial number of spinal neurons survive despite severe symptoms of motor and sensory deficit arising from the secondary lesion process that extends, within the first 24 hr, the pathological degeneration to initially spared spinal areas (Ahuja et al., ; Dell'Anno & Strittmatter, ; Filous & Schwab, ; Kuzhandaivel, Nistri, Mazzone, & Mladinic, ; Quraishe, Forbes, & Andrews, ). This observation is corroborated by clinical studies (Hoh, Mercier, Hussey, & Lane, ; Kaelan, Jacobsen, & Kakulas, ; Squair, West, & Krassioukov, ). The question then arises about the nature of the intrinsic protective mechanisms that can avoid a more extensive neuronal damage.…”
Section: Introductionsupporting
confidence: 66%
“…The prevailing explanation for the characteristic decline in LV dimensions is reduced venous return resulting from the loss of descending sympatho‐excitatory control from the rostral ventrolateral medulla (Krassioukov & Fehlings, ; Squair et al . ) as well as reduced muscle pump activity (Raymond et al . ; Faghri & Yount, ) and impaired venous compliance (Wecht et al .…”
Section: Discussionmentioning
confidence: 99%
“…Patients with spinal cord damage often suffer from cardiovascular disease, a leading cause of death for these individuals [ 65 ]. Following SCI, autonomic nervous system impairment results in blood pressure and heart rate dysregulation [ 66 ].…”
Section: Role Of Inflammation and Immunity In Post-sci Complicationsmentioning
confidence: 99%